Cztery rodzaje edukacji gerontologicznej w Polsce – sytuacja obecna i przyszłe potrzeby - Szarota, Zofia; Perek-Białas, Perek-Białas (Studia Edukacyjne, 2020)
An increased interest in gerontological (old age) education has been recently observed in Poland. It is moreover claimed that this discipline has undergone a rapid development. This observation is particularly true in the context of the Universities of Third Age (U3A) movement. In this paper, we would like to revise current concepts, developed for the purpose of gerontological education, and then contribute to the overall discussion to stress that there is a need to include all education-oriented activities related to old age and ageing in various aspects as one integrated theoretical concept. We would like to address this topic in a holistic manner. However, we aim to connect the aspect of the recent development of old age-focused educational activities carried out in Poland with some data that has not been published before. This will provide an option to understand the development of education of these concepts in Poland as well as help to identify the drawbacks of this process. We will contribute an in-depth evaluation of this process in Poland and outline future needs which have to be met to use all opportunities to prepare both the present and future society for the rapid ageing of Poland’s population.